Hepatotoxicity-Related Adverse Effects of Proton Pump Inhibitors: A Cross-Sectional Study of Signal Mining and Analysis of the FDA Adverse Event Report System Database - Zeng, Yifan; Dai, Ying; Zhou, Ziye; Yu, Xuben; Shi, Dawei (Frontiers in Medicine, 2021)
Background & Objectives: Mounting evidence demonstrates that proton pump inhibitors (PPIs) are associated with a number of adverse effects. However, the literature about hepatotoxicity-related adverse effects (HRAEs) of PPIs are mostly case reports and a few clinical studies. Methods: We evaluated the association between PPIs and HAREs using the reporting odd ratio (ROR) for mining the adverse event report signals in the FDA Adverse Event Reporting System (FAERS) database. Results: There were 23825 reports of PPIs as primary suspect drug or second suspect drug, of which 3253 reports were HRAEs. The top five HRAE signals caused by PPIs were cholestatic hepatitis, cholestasis, fulminant hepatitis, subacute hepatic failure, and acute hepatitis. We also summarized the signals of the HRAEs caused by each PPI. The simultaneous signals were cholestasis and hepatitis cholestatic. For the cholestasis signal, Esomeprazole showed an ROR of 21.556 (95% CI 17.592-26.413); Pantoprazole showed the highest ROR of 22.611 (95% CI 17.794-28.733) in the hepatic cholestatic signal; Lansoprazole was the only PPI with expression in the coma hepatic signal, with an ROR of 10.424 (95% CI 3.340-32.532). By analyzing the reports of Pantoprazole-induced hepatic encephalopathy, we found that patients aged over 65 years and males reported the highest rate. And from the combination of drugs and indications of drugs, no intentional results were obtained. Conclusions: The RORs of signals of “cholestasis” were generally higher than those of “hepatocellular injury”. And the signals about “cholestasis” in HRAE caused by PPIs are more reported.